2017
DOI: 10.5433/1679-0359.2017v38n4p2141
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of concentrate supplementation for grazing beef cattle

Abstract: The objective of this study was to evaluate the effects of frequency of concentrate supplementation on the daytime feeding behavior (grazing, rumination, drinking, and idle times), production performance, and economic viability of grazing cattle in the rainy season. A total of 120 uncastrated Nellore animals with an average body weight (BW) of 382.5 ± 32.2 kg were allocated to palisadegrass (Brachiaria brizantha) paddocks for the experiment. We evaluated supplements provided in the amount of 2.0 kg/ animal, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…Many low input, predominantly non-irrigated livestock systems have little impact on freshwater resources from consumable water use [73]. Due to the higher proportion of concentrate in the diet, the total water consumption per hectare and per kg of beef body weight by animals is higher for GS consistent with prior research [32,74]. Our simulated water use for pasture improvements was higher per kg of beef body weight (BW) compared to extensive, but was lower per hectare in the Cerrado (−13%) and Amazon (−5%) biomes (Supplementary Materials, Table S4).…”
Section: Carbon Emissions Water Energy and Nitrogen Impacts Of Intsupporting
confidence: 71%
“…Many low input, predominantly non-irrigated livestock systems have little impact on freshwater resources from consumable water use [73]. Due to the higher proportion of concentrate in the diet, the total water consumption per hectare and per kg of beef body weight by animals is higher for GS consistent with prior research [32,74]. Our simulated water use for pasture improvements was higher per kg of beef body weight (BW) compared to extensive, but was lower per hectare in the Cerrado (−13%) and Amazon (−5%) biomes (Supplementary Materials, Table S4).…”
Section: Carbon Emissions Water Energy and Nitrogen Impacts Of Intsupporting
confidence: 71%
“…Varios autores han relacionado el efecto positivo de reducir la frecuencia de suplementación sobre los costos operativos en sistemas de producción de carne, como una consecuencia directa del menor gasto en mano de obra, combustible, horas de trabajo en máquina, entre otros (de-Paula et al, 2010;de-Figueiredo et al, 2015;Bonadimann et al, 2017). En el presente trabajo no se registró una ventaja comparativa entre las frecuencias de suplementación y el tratamiento sin suplementación, probablemente motivado por la poca respuesta biológica en ganancia de peso asociada a las dietas, las cuales no lograron compensar el costo incremental en el suministro del alimento y a la calidad nutricional de las pasturas evaluadas.…”
Section: Cynodon Nlemnfunsisunclassified
“…Reducing the frequency of supplementation can reduce labor and transportation costs, with potential for increased profits (DREWNOSKI; POORE, 2012). Bonadimann et al (2017) found that the supplementation concentrated in three times a week did not affect the performance of animals but led to a reduction in the distribution of labor costs necessary to provide concentrated supplement during the rainy season.…”
Section: Introductionmentioning
confidence: 96%